PENGARUH SUASANA HATI TERHADAP PROKRASTINASI AKADEMIK PADA MAHASISWA PSIKOLOGI - Berutu, Ncihur E.; Putri, Ni Luh; Hartati, Meike E. (PSIKOPEDIA, 2024)
The purpose of this study is to determine whether there is an influence of mood on academic procrastination in psychology students class of 2022. This research is a quantitative research with a population of all Psychology students class of 2022 at Manado State University which amounts to 250 students. The sample size was 130 students determined by Isaac and Michael’s table, and simple random sampling techniques. The hypothesis test in this study is Simple Linear Regression, using statistical tests with the help of SPSS Version 26. The results of a simple linear regression test obtained an R Squer value of 0.246 or 24.6%. The regression equation is obtained Y = 4.441 + 0.954X, which means that the constant value is 5.395 with a regression coefficient of 0.954. As for the value of sig. 0.000 < 0.05 which means that if the significance value is <0.05 then it can be concluded that Ha is accepted and Ho is rejected.